Söderwall Supplement - Språkbanken Text (University of Gothenburg, 2024)
The lexicon consists of K.F. Söderwall's Ordbok Öfver svenska medeltids-språket. Supplement. Vol IV—V. (Lund 1953—1973), with about 21,000 entries.

The dictionary has been manually encoded at Språkbanken, University of Gothenburg. The entries have not been proofread after encoding.

Lexikonet består av K.F. Söderwalls Ordbok Öfver svenska medeltids-språket. Supplement. Vol IV—V. (Lund 1953—1973), med ca 21.000 uppslagsord.

Ordboken har kodats in manuellt vid Språkbanken, Göteborgs universitet. Uppslagsorden och övriga delar av ordboksartiklarna är inte kontrollästa efter inkodningen.
Söderwall Supplement
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik